INTERNATIONAL FOOD TRADE IN THE CONTEXT OF WATERFOOTPRINT MANAGEMENT - Lukić, Dušan N.; Radosavljević, Milan; Radosavljević, Dragana (ACADEMIC REVIEW, 2024)
Water as a mostly local resource is characterized by dynamic imbalance. The imbalance is depicted in sufficient quality water supply in relation to demand, deficiency od the optimal infrastructure, as well as inadequate management of systems. The implemented water per unit of produce, foods which are traded on the global market, is much higher than the amount of water present in the final produce themselves. The calculation framework of water footprint depends on the level of urban needs and agricultural, energy and industrial sectors capacity. Meanwhile, agriculture is identified as the leading user of water resources during the production process as well as in terms of the negative side effects used water has on existing water quality. The increase of agricultural production, economical, trade and investment interactions during trade on global level are present. These become conditio sine qua non optimally perceived factors of production and their utilization during production of various goods. The aim of this paper is analysis of water footprint and potential saving of water components from the perspective of production and consumption, resulting from international food trade.